The Effects of Mergers and Acquisitions on the Firm Size Distribution - Elena Cefis; O. Marsili; E.J.J Schenk (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
This paper provides new empirical evidence on the effects of mergers and acquisitions on the shape of the firm size distribution (FSD), by using data of the population of manufacturing firms in the Netherlands. Our analysis shows that M&As do not affect the size distribution when we consider the entire population of firms. When we focus on the firms involved in a M&A event, we observed a shift of the FSD towards larger sizes. FSD becomes more concentrated around the mean size, less skewed to the right hand side, and thinner at the tails as a whole. The shift toward higher sizes due to M&A is not uniform but affects firms of different sizes in different ways. While the number of firms in the lower tail decreased, the number of firms in the central size classes increased substantially and out weighed the increase in the number (and mean size) of firms in the upper tail of the distribution (consequently the overall market concentration measured by the Herfindhal index declines). M&As leads to a departure from log-normality of the FSD, suggesting that external growth does not follow a Gibrat's law. Our counterfactual analysis highlights that only internal growth does not affect the shape of the size distribution of firms. On the contrary, it suggests that the change in the size distribution is almost entirely due to the external growth of the firms.
Keywords: 330; firm size distribution; Mergers and Acquisitions; firm entry and exit; industry concentration